Adsorption of Isonicotinamide on Loughlinite (Natural Na-Sepiolite): An FT-IR Spectroscopic Study - Akyuz, Sevim; Akyuz, Tanil (Asian Journal of Chemistry, 2014)
In this study adsorption of isonicotinamide on loughlinite (Na-sepiolite) has been investigated by FT-IR spectroscopy. The adsorption of isonicotinamide showed a considerable alteration on both Si-OH stretching and deformation peaks of loughlinite structure. Spectroscopic results indicate that adsorbed isonicotinamide molecules onto loughlinite are coordinated to surface silanol groups and/or Lewis acidic centers by H-bonding interaction through pyridine ring nitrogen lone pairs. The amino nitrogen is found to be relatively in active to adsorbing sites.